Education programs for young people in the fields of architectural formatting, heritage, urban and spatial planning - Danilović Hristić, Nataša; Nenković-Riznić, Marina; Simonović Alfirević, Sanja (Arhitektura i urbanizam, 2022)
In professional circles, it often seems that the state of our urban environment and attitude towards the natural environment reflect a lack of attention devoted to educating all generations, and a lack of awareness raised on this topic. The picture of our settlements is actually a picture of ourselves. For this reason, and the desire to draw young people in and explain professional topics to them in an adequate and acceptable way, and to develop a love of the environment and awareness of the quality of life, several institutions and organizations have launched independent education programs. These programs and workshops are implemented partly voluntarily, or within activities related to specific events and projects and the regular activities of individual institutions, and they are designed as a supplement to educational programs in preschools, schools and universities. The paper analyzes known approaches, methods and techniques related to youth participation, shown through a selected review of the literature. Also cited are examples of several different educational workshops in some of Belgrade’s professional institutions and organizations, based on architectural formatting, urban planning, the protection of built heritage and the preservation of ecological corridors. Based on the experiences acquired and the observed results, a series of recommendations are formed for the organization and implementation of this form of education. The aim of the research is to highlight the importance, possibilities and benefits of educating young people in terms of understanding and caring for the space that surrounds us, as well as others with whom we share that space. Participation in the creative process contributes to gathering observations, ideas, visions and expressing needs, with the possibility of their application.
Keywords: education; children; urbanism; participation; workshops